Surgical oncological emergencies in octogenarian patients - Friziero, Alberto; Sperti, Cosimo; Riccio, Federica; Zuin, Irene Sole; Vallese, Lorenzo; Serafini, Simone; Amico, Alessandra; Valli, Valeria; Da Re, Chiara; Baldan, Nicola; Valmasoni, Michele; Da Dalt, Gianfranco (Frontiers in Oncology, 2023)
Background Surgical oncological emergencies represent a frequent challenge in acute settings, with postoperative courses characterized by high morbidity and mortality. An accurate selection of patients who could benefit from surgery is essential to avoid unnecessary invasive treatment. In this study, we tried to determine if advanced age (>80 years) represents a risk factor for negative short-term outcome in patients undergoing emergency surgery for acute abdominal oncological illness. Methods We retrospectively analyzed the records of patients who underwent emergency oncological surgery at the Department of Acute Care Surgery of Padua General Hospital from January 2018 to December 2022. One hundred two cancer patients were included in the study. Among them, 42 were aged ≥80 years (41%). Multiple preoperative and postoperative parameters were recorded, and the follow-up period was at least 90 days. Multivariate logistic regression analyses were used to identify factors associated with short-term postoperative outcomes. Results In the octogenarian group, 30-day mortality was 11% vs. 9.5% in the younger group [p = not significant (ns)] and 90-day mortality was 17.6% in the octogenarian group vs. 20.5% in the younger group (p = ns). Postoperative morbidity and hospital length of stay were not significantly different in the two groups. Low albumin levels [odds ratio (OR) 30.6, 9.51–87.07] and elevated lactate dehydrogenase (LDH) levels (OR 26.4, 9.18–75.83) were predictive for short-term mortality in surgical oncological emergencies. Conclusion Advanced age is not a risk factor for negative outcomes in surgical oncological emergencies. Therefore, surgical options should be considered in octogenarians with oncological emergencies and acceptable clinical conditions. Serum albumin levels and LDH can help predict the postoperative outcome after surgery for oncological emergencies.